Journal of Eating Disorders - Hay, Phillipa; Touyz, Stephen; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Journal of Eating Disorders is the first Gold open access, peer-reviewed journal publishing leading research in the science and clinical practice of eating disorders. It disseminates research that provides answers to the important issues and key challenges in the field of eating disorders and to facilitate translation of evidence into practice. The journal publishes research on all aspects of feeding and eating disorders namely their epidemiology, nature, determinants, neuroscience, prevention, treatment and outcomes. The scope includes, but is not limited to anorexia nervosa, bulimia nervosa, binge eating disorder, ARFID, and other eating disorders. Related areas such as important co-morbidities, high weight/obesity, body image, appetite, food and eating are also included where relevant to eating disorders. Articles about research methodology and assessment, as well as case series/reports and commentaries are welcomed where they advance the field of eating disorders.
Keywords: Psychology; Medicine, Preventive; Health promotion; Psychiatry; Clinical psychology; Psychobiology; Human behavior; Psychology$1 (BMethodology.s; Behavioral Sciences and Psychology; Health Promotion and Disease Prevention; Psychiatry; Clinical Psychology; Behavioral Neuroscience; Psychological Methods